Does Illness Perception Predict Posttraumatic Stress Disorder in Patients with Myocardial Infarction? - (:unkn) unknown (AVES, 2014)
Introduction: Myocardial infarction (MI) as a life-threatening event, carrying high risk of recurrence and chronic disabling complications, increases the risk of developing acute stress disorder (ASD), posttraumatic stress disorder (PTSD), or both. The aim of this study was to investigate the relationship between illness perceptions and having ASD, PTSD, or both in patients after MI. Method: Seventy-six patients diagnosed with acute MI were enrolled into our prospective study. We evaluated patients during the first week and six months after MI. Patients were assessed by using the Clinician Administered PTSD Scale (CAPS), the Hamilton Depression Rating Scale (HDRS), the Hamilton Anxiety Rating Scale (HARS), the Brief Illness Perception Questionnaire (BIPQ), and a semi-structured interview for socio-demographic characteristics during both the first and second evaluations. Results:Acute stress disorder (ASD) developed in 9.2% of patients and PTSD developed in 11.9% of patients with MI. Illness perception factors of 'consequences, identity and concern' predicted the occurrence of both ASD and PTSD, whereas 'emotion' predicted only PTSD. Conclusion: The factors of illness perceptions predicted the induction of ASD and PTSD in patients who had acute MI.
Keywords: Acute stress disorder; illness perception; myocardial infarction; posttraumatic stress disorder; CORONARY-ARTERY DISEASE; QUALITY-OF-LIFE; CARDIAC REHABILITATION; HEART-DISEASE; DEPRESSION; PREVALENCE; SYMPTOMS; NONADHERENCE; ASSOCIATION; ATTENDANCE